Exploring Perceptions of Ohio Residents on Agricultural Issues - Manita Thapa; Sudarshan Adhikari; Annie R. Specht; Cara Lawson; Joy N. Rumble; Emily B. Buck (Journal of Applied Communications, 2025)
Agricultural issues are the topics that attract public attention and impact the sector. This study investigated the salient agricultural issues and perceptions on those issues among Ohio residents. The study employed agenda setting theory to understand how media shapes public perceptions of agricultural issues in Ohio. A quantitative method was used, and a survey instrument was developed after an environmental scan of selected sources to identify five issue categories. From the responses of 515 Ohio residents, the findings suggest that environmental issues, particularly water quality, were the most important among participants. Food quality followed, focusing on aspects like safety, quality, and sustainability. Climate change, animal welfare, and government policy ranked third, fourth, and fifth in importance, respectively. Participants presented a moderate level of awareness about climate change, with a greater emphasis on the conservation of public lands and forest management. In terms of government policy, the recognition of the need to balance economic and environmental interests was observed with a desire for farmland preservation. Additionally, participants perceived food as expensive, with moderate in quality and healthiness. While perceptions of climate change issues were moderate, they acknowledged that the role of human behavior in environment management is paramount. Participants’ perception of livestock treatment indicated their concerns for animal welfare. The perceptions toward government policies reflect the recognition of the economic importance of the agricultural sector, yet there is apparent dissatisfaction at the same time. These findings served as a foundation for targeted interventions, stakeholder collaborations, and policy enhancements in addressing agricultural issues.
Keywords: Agenda Setting; Salient Issues; Public Perceptions